Konservasi Sumberdaya Alam Tambang Marmer Dalam Tinjauan Perspektif Islam (Studi Kasus PT. Industri Marmer Indonesia Tulungagung Kecamatan Besuki) - Maya Zulfa Maslihatin; Moh. Qudsi Fauzy (Universitas Airlangga, 2016)
Conservation is a way of management which is done by men in using natural resources so that it can provide benefit and maintain the potentials to meet the needs and aspirations of the future generations. This research aims to find out the marble mine natural resources conservation in PT.Industri Marmer Indonesia Tulungagung within Islam's point of view. This research uses qualitative approach. Data collection is done by using interviews and direct observations towards the research object. Data checking is done by using triangulation byinvolving observations, interviews and documentions.The results show that the economic conservation implementation of natural resources of marble mine in Islam's point of view has been implemented and done by PT. Industri Marmer Indonesia Tulungagung and also there are positive impacts towards the community in the form of factory waste management.